The Effects of Group Identity on Pro-environmental Behavioral Norms in China: Evidence From an Experiment - Wan, Qinjuan; Deng, Hongping (Frontiers in Psychology, 2022)
This study experimentally evaluates the effects of group identity primed by property right on the pro-environmental behaviors and social norms in an urban Chinese environment. The research in this paper expands the research perspective and method of domestic waste management, and provides a theoretical basis for the establishment of long-term mechanism of environmental treatment. We use two simple binary choice tasks that tests the pro-environmental behaviors (PEB) and environmental types of individuals. This is one of the earliest test for group identity and social norms in pro-environmental examination in Chinese. Our results reveal that: (i) publicity and education has a significant positive effect on the development of individual and group pro-environmental behavioral norms; (ii) housing ownership has no differentiating effect on individual environmental behavior; and (iii) the development of social norms of pro-environmental behavior varies according to group conditions, which in turn determines individual environmental behavioral choices and types of environmental behavior. The results also suggest that PEB might be shaped and norms built by group conditions other than group identity.